PENERAPAN ALGORITMA APRIORI DAN ALGORITMA FP-GROWTH DALAM MENEMUKAN HUBUNGAN DATA NILAI IJAZAH MATEMATIKA DAN BAHASA INGGRIS DENGAN NILAI MATA PELAJARAN PEMROGRAMAN DAN WEB PROGRAMMING (STUDI KASUS SMK SANDIKTA KELAS X BEKASI) - MAULANA MAULANA (Institut Bisnis Muhammadiyah Bekasi, 2020)
In comparing objects to analyze the relationship between objects, in computer technique, we can use the methods called data mining. This system is very familiar created with many steps. In this research, algorithm ways used is algoritma priory and algorithm FP- Growth. To decide the relationship between scores in Math and English and the final result of programming and web programming study, we use the two methods above. So, we can see the relationship between the three indicators mentioned. The connection of math and programming, the highest confidence score was 54.5%. The connection between English and programming was 66.7% and the connection between English and web programming was 60%. For the result of the FP-Growth Algorithm process, the high difference was seen in a simpler and faster way, compared if using apriori. This is caused by the reason Algorithm FP-Growth, not all data scanned to get the scoring support based on frequencies from each data given.